Transmission of 344 Gb/s 16-QAM Using a Simplified Coherent Receiver Based on Single-Ended Detection - Thang M. Hoang; Mohammed Y. S. Sowailem; Mohamed Morsy-Osman; Mathieu Chagnon; David Patel; Stephane Paquet; Carl Paquet; Ian Woods; Odile Liboiron-Ladouceur; David Plant (IEEE Photonics Journal)
We demonstrate a single-wavelength, 344-Gb/s, 43-Gb 16-quadrature amplitude modulation (QAM) polarization division multiplexed signal transmission over 800 km operating below the hard-decision forward error correction (FEC) BER threshold of $3.8× 10^{-3}$ using an InP dual-polarization in-phase/quadrature modulator. At the receiver, a simplified single-ended coherent receiver with novel digital signal processing (DSP) for self-beating noise removal is employed. Compared with the conventional single-ended detection, this signal processing method doubles the propagation distance and increases the SNR by more than 1 dB. In addition, this DSP method provides 10 dB of the received optical power dynamic range while operating below the hard-FEC BER threshold of $3.8× 10^{-3}$ , compared with the no dynamic range for a single-ended receiver without the proposed DSP.